Missing Page Book Story Media to Stimulate Listening in Children 5-6 Years - Aida Fitria, Salsabila; Gunarti, Winda; Syamsiatin, Eriva (Exploration in Early Childhood Research, 2024)
This action research activity uses the Research and Development (R&D) method by developing a product, namely  to overcome problems related to media needs to stimulate children's listening skills. The implementation of media usage trials was carried out on children aged 5-6 years at BKB PAUD Hasanah. The research instruments used were observation, interviews, questionnaires and documentation. The data analysis technique uses qualitative descriptive analysis of the flow model type and quantitative descriptive analysis through a Likert scale and Guttman scale. Based on the data obtained regarding children's listening skills in the first trial of 87.5% and the second trial of 98.4%. In addition, media assessment data from expert judgment and teachers were obtained. Material experts amounted to 92.10% while the percentage obtained from media experts was 90.9% and the teacher's assessment obtained an average percentage score of 87%. So it can be said that the  media is declared feasible to be developed and tested in the field.